Risks and countermeasures of artificial intelligence generated content technology in content security governance - Zhe QIAO (Dianxin kexue)
Recently, artificial intelligence generated content (AIGC) technology has achieved various disruptive results and has become a new trend in AI research and application, driving AI into a new era.Firstly, the development status of AIGC technology was analyzed, focusing on generative models such as generative adversarial networks and diffusion models, as well as multimodal technologies, and surveying and elaborating on the existing technological capabilities for text, speech, image and video generation.Then, the risks brought by AIGC technology in the field of content security governance were focused and analyzed, including fake information, content infringement, network and software supply chain security, data leakage and other aspects.Finally, in view of the above security risks, counter strategies were proposed from the technical, application and regulatory levels, respectively.